New records of rare genera of the subfamily Cheloninae (Hymenoptera: Braconidae), with description of two new species from Vietnam - Long, Khuat Dang; Duong, Nguyen Van; Hoa, Dang Thi (Academia Journal of Biology, 2019)
New species of subgenus Areselonus Braet, 1999 and genus Odontosphaeropyx Cameron, 1910, viz. Chelonus (Areselonus) intermedius Long, sp. n. and Odontosphaeropyx plesius Long, sp. n. (Braconidae: Cheloninae) are described and illustrated. Additionally, these two rare taxa are newly recorded for Vietnam’s braconid fauna. The checklist and distribution of the already known species of the genera are also provided.